In this textbook i am looking at it says:(adsbygoogle = window.adsbygoogle || []).push({});

"Thus e^y + e^-y =2x or

e^2y - 2xe^y + 1 = 0"

how did they go from the first to the second part?

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# E^y + e^-y =2x or e^2y - 2xe^y + 1 = 0 equation

**Physics Forums | Science Articles, Homework Help, Discussion**